Can you please help me with this.
Attachments:
![](https://hi-static.z-dn.net/files/d2b/0d82798bc6ac9b45b36ec064580700f2.jpg)
Answers
Answered by
0
√3(√7-√3)
= √21 - 3
= √21 +(-3)
= √a + b
by comparing we get a = 21 & b = -3
hence this is the required answer
= √21 - 3
= √21 +(-3)
= √a + b
by comparing we get a = 21 & b = -3
hence this is the required answer
Similar questions
Science,
8 months ago
Political Science,
8 months ago
Physics,
8 months ago
Physics,
1 year ago
Physics,
1 year ago
Environmental Sciences,
1 year ago
English,
1 year ago